Followed The Regularized Leader (FTRL) prediction model based photovoltaic array reconfiguration for mitigation of mismatch losses in partial shading condition. Issue 1 (12th September 2021) - Gao, Xin; Deng, Fang; Zheng, Hao; Ding, Ning; Ye, Ziman; Cai, Yeyun; Wang, Xiangyang
Abstract: Non‐uniform irradiance, for example, partial shading, would affect the performance of the whole Photovoltaic (PV) array and reduce the output power. Since the layout of PV array is also an important factor influencing the performance of PV array, reconfiguration scheme has been researched popularly. Since plenty of array reconfiguration techniques are not realistic to be implemented in reality, in this paper considering the simplicity, robustness and economical aspects, a Followed The Regularized Leader algorithm (FTRL) regression prediction model based switches controlled PV array reconfiguration method is proposed to enhance the power output from solar PV array and alleviate the effects of partial shadings. The proposed scheme has no additional labor and wire requirement, since the proposed connection architecture of PV array involves no complex switch matrix design. Subsequently, to testify the performance of the proposed scheme, simulations with various shades in different PV arrays are made and evaluation parameters, for example, Fill Factor (FF) and mismatch loss are calculated. Furthermore, outdoor experiments are conducted to validate the simulation and the analyses. Besides, extensive analyses of cost analysis and energy savings are given. At last, a comprehensive evaluation is performed to check the quality of the proposed scheme by comparing with various techniques in literature.